2013
DOI: 10.1108/20421161311288866
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence Iranian students’ decision to choose accounting major

Abstract: Purpose -The aim of this study is to explore whether there are statistically significant differences in the influence that various career-choice factors may have on a decision to choose accounting and non-accounting majors in Iran. The findings derived from this study could assist accounting educators and professional accounting bodies to understand the reasons why students may want to choose an accounting major. In this regard, the findings could help accounting academics and the policy makers in the accounti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 30 publications
7
47
0
7
Order By: Relevance
“…However, a study on Iranian students did not find a genuine interest in accounting, perception of the accounting course, and perception of the accounting profession significant in influencing students' decision to study accounting (Dalci et al, 2013).…”
Section: Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a study on Iranian students did not find a genuine interest in accounting, perception of the accounting course, and perception of the accounting profession significant in influencing students' decision to study accounting (Dalci et al, 2013).…”
Section: Interestmentioning
confidence: 99%
“…According to Dalci, Arasli, Tumer, & Baradani (2013), referents (parents, teachers, career advisors and peers) were significantly associated with Iranian student's decision to major in accounting. The results also indicated that Iranian students were sensitive to referents' opinions in choosing an accounting major.…”
Section: Familymentioning
confidence: 99%
See 1 more Smart Citation
“…This study accepts the latter definition. Understanding students' perceptions of accountancy profession is an important step in identifying the students' intention in pursuing the professional qualification as students' career choice is highly influenced by students' belief that was formed through perception [7,8]. Literature on perception in relation to accounting may be classified into perception on accounting as a profession [9,10], which would affect perception of students in taking accounting as a major [11,12] as well as perception of students to become professionally qualified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…IFIs could consider organizing frequent visits to higher institutions and employment roadshow to public, informing the "positive sides" of the profession such as vast employment opportunities available in the industry and long term career prospect (Dalci, Arasli, Tumer et al, 2013) particularly on shari'ah auditing.…”
Section: Islamic Finance 93mentioning
confidence: 99%